Surgical treatment of non-neoplastic ovarian tumors - Alvarez Bravo, Alfonso (2015)
Speaking of ovarian tumors which are to be considered non-neoplastic there are differences of opinion. Thus, p. ex. Goodall (7) agree that follicular cysts and corpus luteum cysts are neoplasms; and many others including Barzilai (4) and Geist (6) classified among non-neoplastic tumors have no real growth of its structural elements, and finally, others such as Ahumada et al (1), considered undeserving even the name of tumors.